Prevalence of endoparasites in children from the rural area of Cáceres-MT (Research, Society and Development, 2021)
Enteroparasites are common in individuals who are under precarious conditions of housing, cleans water, basic sanitation and hygiene. The objective of this study is to verify the prevalence of intestinal parasitosis in school-age children from the Paiol settlement/community, in the city of Cáceres-MT. Parasitological analyzes using the Hoffman method, in addition to socioeconomic and environmental data, were performed in 75 samples of children aged 7 to 16 years. The overall prevalence of intestinal parasites was 56% in the studied population. Protozoa were identified in 98% of positive samples, with Blastocystis hominis being the most prevalent, followed by Endolimax nana, Entamoeba coli, and Giardia lamblia. Helminths were identified in 5% of the total samples analyzed, with Trichuris trichiura and Hymenolepis nana being the only ones identified. It is concluded that there is a high prevalence of intestinal parasite in children, especially of intestinal protozoa, requiring improvements and monitoring of hygienic-sanitary conditions in rural communities in the studied region.